Penaksiran Dan Pengujian Model Regresi Beta-Logistik Heckman-Willis - Nusar Hajarisman; Asep Saefuddin (FORUM STATISTIKA DAN KOMPUTASI, 2001)
Methods are presented for modeling dose-related effects in proportion data when extra-binomial variability is a concern. Motivation is taken from experiments in developmental toxicology, where the observed proportions. Appeal is made to the well-known beta-binomial distribution to represent the overdispersion. From this, an exponential function of the linear predictor is used to model the dose-response relationship. The spesification was introduced previously for econometric applications by Heckman and Willis; it induces a form logistic regression for mean response, together with a reciprocal biexponential model for the intralitter correlation. For large sample, likelihood based methods for estimating and testing the joint proportion-correlation response are studied.Keywords: logistic regression, beta-binomial distributin, biexponential model